Early Holocene phytolith records for three shell midden sites, Yongjiang River, Guangxi Province, China. (January 2021) - Zhang, Yekun; Huang, Shengmin; Chen, Weiju; Qin, Fang; Pu, Xiaodong; Wei, Wenheng; Huang, Miaomiao; Wood, Rachel; Denham, Tim
Phytolith records from three proximal freshwater shell midden sites document plant exploitation and local palaeoecological changes during the early Holocene in present-day Nanning City, Guangxi Province, China. Radiocarbon dating of freshwater gastropod shells indicates the midden sites formed sequentially, with variable chronological overlaps: Baozitou at 12, 000-11, 130 cal BP, Shichuantou at 11, 250-10, 500 cal BP and Nabeizui at 11, 060-9560 cal BP. Palaeoecological data are inferred to show variable trends of forest reduction or recovery during the formation of each midden, suggesting different intensities of site use and impacts upon the local environment. Significantly, palms (Arecaceae) became more frequent during the middle period of formation at each site, which is interpreted to represent resource intensification and selective exploitation of palms by the communities who created each midden.